The educational tours in the school educational project as a tool to work skills and promoting the practice of cooperative work in the teacher work teams and with students - Ángel de la Fuente Martínez (ADIDE Federación, 2015)
The educational tours are a methodological strategy for working all competitions and facilitates the implementation of the principles of interdisciplinarity, coordination and cooperative work not only among teachers but among teachers. It also allows you to schedule and sequence curriculum based on projects, making learning significant. The definition of areas, activities and departments involved gives us insight to guide planning the itinerary, complete with a selection of six photographs and a map of the route developed by the undersigned. Once you know what we offer and what we can work explains how incardinated each of the skills and teamwork, concluding that such activities on the sidewalk knowledge to students and helps them apply it in different contexts. That is the essence of meaningful learning, building learning bailing lessons learned while acquiring new knowledge.